THE INFLUENCE OF ORGANIZATIONAL CULTURE AND COMPETENCE ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE (STUDY AT PT AEL INDONESIA SITE KPC EAST KALIMANTAN) - Sultan S. Saade; Theresia Pradiani; Fathorrahman Fathorrahman (Sean Institute, 2023)
Blasting is an important aspect of the mining process to improve the efficiency of mineral and coal recovery. PT AEL Indonesia, one of the blasting service companies, is committed to fulfilling its responsibility to customers by achieving performance targets and conducting safe blasting. Customer surveys show that customer satisfaction with PT AEL Indonesia's performance at KPC Site is below the minimum target of 80%. Employee performance is one of the contributing factors, indicated by a series of human error misfires, vehicle operation incidents and activities that do not follow the procedures. The company needs to pay attention to the factors of organizational culture, competence and work motivation as important factors that affect their performance. The purpose of this study was to provide an analysis of the mainstreaming of organizational culture and competence on employee performance with work motivation as an intervening variable at PT AEL Indonesia Site KPC East Kalimantan. The data used in this study are primary data obtained from the results of distributing questionnaires. Sample determination is done by non-random sample method (non-probability sampling) with a saturated sample procedure (census) with a sample size of 158 people. The research data were processed quantitatively description with path analysis techniques and sobel test using SPSS ver 21. The results of the study concluded that (1) Organizational culture has a positive and significant effect on work motivation, (2) Competence has a positive and significant effect on work motivation, (3) Organizational culture has a positive and significant effect on employee performance, (4) Competence has a positive and significant effect on employee performance, (5) Work motivation has a positive and significant effect on employee performance, (6) Indirectly, organizational culture through work motivation does not significantly affect employee performance, (7) Indirectly, competence through work motivation does not significantly affect employee performance.Keywords: Organizational Culture, Competency, Job Motivation, Employee Performance.